2022
DOI: 10.1097/mpa.0000000000002164
|View full text |Cite
|
Sign up to set email alerts
|

DPP10-AS1–Mediated Downregulation of MicroRNA-324-3p Is Conducive to the Malignancy of Pancreatic Cancer by Enhancing CLDN3 Expression

Abstract: Objectives: Network of long noncoding RNA-microRNA (miRNA)-mRNA is becoming increasingly pivotal roles in carcinogenesis mechanism. Herein, we aim to delineate the mechanistic understanding of dipeptidyl peptidase like 10-antisense RNA 1 (DPP10-AS1)/miRNA-324-3p/claudin 3 (CLDN3) axis in the malignancy of pancreatic cancer (PC).Methods: Microarray profiling and other bioinformatics methods were adopted to predict differentially expressed long noncoding RNA-miRNA-mRNA in PC, followed by verification of expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…shown to increase the engagement of PC [9][10][11] . For instance, Terashima et al revealed that lncRNAmaternally expressed (MEG)8 and MEG3 promote epithelial-to-mesenchymal transition (EMT) in PC cells by stimulating SNAIL and the zinc nger E-box-binding homeobox (ZEB) protein family of EMTtranscription factors (TF) 12 .…”
Section: Introductionmentioning
confidence: 92%
“…shown to increase the engagement of PC [9][10][11] . For instance, Terashima et al revealed that lncRNAmaternally expressed (MEG)8 and MEG3 promote epithelial-to-mesenchymal transition (EMT) in PC cells by stimulating SNAIL and the zinc nger E-box-binding homeobox (ZEB) protein family of EMTtranscription factors (TF) 12 .…”
Section: Introductionmentioning
confidence: 92%